Menelusuri Jejak Hijau: Hubungan Antara Profitabilitas, Leverage, dan Pengungkapan Emisi Karbon - Heru Amrasyid; Irda Rosita; Lisa Amelia Herman (Politeknik Negeri Padang, 2025)
This study explores the dynamics of how profitability and leverage influence carbon emissions disclosure among companies. Utilizing the Wald test for partial analysis and the Omnibus Test for simultaneous evaluation, we found that profitability does not significantly impact carbon emissions disclosure. In contrast, leverage demonstrated a significant influence, indicating that companies with higher levels of debt tend to be more proactive in disclosing information related to carbon emissions. These findings reflect companies' efforts to maintain their reputation and meet stakeholder expectations amid growing awareness of environmental issues. The study also acknowledges its limitations, such as focusing on a specific sector and not considering other potentially relevant variables. Therefore, future research is recommended to incorporate additional variables and qualitative approaches to provide deeper insights into the increasingly important practice of sustainability disclosure in the modern business context.